Topological Entropy of Linear Operations - Herrmann, John; Kelly, James; Lutz, Eli (Topology Proceedings, 2024)
We discuss the topological entropy of linear operators, specifically examining how the entropy is related to the operator’s spectrum and to its norm. With a specific focus on linear operators on infinite dimensional Banach spaces, we show how the eigenvalues, the spectral radius, and the operator norm can be used to construct lower and upper bounds for the topological entropy.